Boron Levels in Drinking Water Sources from the Volcanic Area of Sicily (South Italy): Risk Evaluation of Developing Chronic Systemic Effects - Chiara Copat; Maria Fiore; Alfina Grasso; Giovanni Arena; Angela Dimartino; Gea Oliveri Conti; Salvatore Sciacca; Margherita Ferrante (Annals of Environmental Science and Toxicology - Peertechz Publications, 2016)
Short- and long-term oral exposures to boric acid or borax demonstrated boron toxicity in reproductive system. European Union standard of boron in drinking water has a maximum allowable concentration of 1 mg/L, but in Sicily (south Italy) there are often higher concentrations. Accordingly, the main objectives of this study, the first of its kind in the south Italy, were (1) to monitor the boron levels in drinking water sources from Mt. Etna, and (2) to estimate the daily intake (EDI) and the Target Hazard Quotient (THQ) in adult population to evaluate the risk of developing chronic systemic effects due to drinking boron intake. We divided the study area into five sectors. Mt. Etna water sources, were collected from 2000 to 2014 and were analyzed by inductively coupled plasma - optical emission spectrometry (ICP-OES). We found boron mean values ranged from 0.199 to 0.863 mg/L with minimum and maximum concentrations of 0.010 and 2.620 mg/L, respectively. Adult EDI concentration was between 0.004 and 0.020 mg/Kg day, thus below the Reference Daily Dose (RfDo) suggested by the Environmental Protection Agency (EPA). THQ always resulted below the level of risk, indicating no risk to develop chronic systemic effects due to drinking boron intake during the lifetime.